The Noteworthiness of Negotiated Understandings on Japanese Flash Fiction Entitled Two Frogs - Pasopati, Rommel Utungga; Napitupulu, Johanes Claudio Perdana; Wulandari, Siti; Wijaya, Kusuma; Kartiningsih, Rindrah (KIRYOKU, 2024)
This article exposes crucial points of negotiated understandings between two characters in Japanese flash fiction entitled Two Frogs. The story tells about the different dreams between two frogs that have plans to reach their destination to see another town. This folktale wants to tell the readers about the similarities between Kyoto and Osaka. Through qualitative method, this research underlines that, in fact, Kyoto is more traditional than Osaka, but later the characters reach such understandings than flourishing the conflicts. Any difference should be negotiated so that it never comes into bigger conflict. Negotiated understanding then could not be separated from such reciprocal cultural appreciations as well. In conclusion, the description, interpretation, and narration of the story explores indications of moral messages of negotiated understandings. It is simply taken as a token of peace that should always be gained rather than unworthy loss due to upcoming frictions between assumptions and interpretations of the characters.